Effectiveness and response predictors of omalizumab in a severe allergic asthma population with a high prevalence of comorbidities: the Australian Xolair Registry. Issue 9 (16th September 2016) - Gibson, P. G.; Reddel, H.; McDonald, V. M.; Marks, G.; Jenkins, C.; Gillman, A.; Upham, J.; Sutherland, M.; Rimmer, J.; Thien, F.; Katsoulotos, G. P.; Cook, M.; et al.
Abstract : Background: Severe asthma is a high impact disease. Omalizumab targets the allergic inflammatory pathway; however, effectiveness data in a population with significant comorbidities are limited. Aims: To describe severe allergic asthma, omalizumab treatment outcomes and predictors of response among the Australian Xolair Registry participants. Methods: A web‐based post‐marketing surveillance registry was established to characterise the use, effectiveness and adverse effects of omalizumab (Xolair) for severe allergic asthma. Results: Participants ( n  = 192) (mean age 51 years, 118 female) with severe allergic asthma from 21 clinics in Australia were assessed, and 180 received omalizumab therapy. They had poor asthma control (Asthma Control Questionnaire, ACQ‐5, mean score 3.56) and significant quality of life impairment (Asthma‐related Quality of Life Questionnaire score 3.57), and 52% were using daily oral corticosteroid (OCS). Overall, 95% had one or more comorbidities (rhinitis 48%, obesity 45%, cardiovascular disease 23%). The omalizumab responder rate, assessed by an improvement of at least 0.5 in ACQ‐5, was high at 83%. OCS use was significantly reduced. The response in participants with comorbid obesity and cardiovascular disease was similar to those without these conditions. Baseline ACQ‐5 ≥ 2.0 ( P  = 0.002) and older age ( P  = 0.05) predicted the magnitude of change in ACQ‐5 in response to omalizumab. Drug‐related adverse events included anaphylactoid reactions ( n  = 4), headache ( n  = 2) and chest pains ( n  = 1). Conclusion: Australian patients with severe allergic asthma report a high disease burden and have extensive comorbidity. Symptomatic response to omalizumab was high despite significant comorbid disease. Omalizumab is an effective targeted therapy for severe allergic asthma with comorbidity in a real‐life setting.